Pengenalan Pajak dalam Kehidupan Sehari-Hari kepada Guru Bimbingan dan Konseling Anggota MGBK (Musyawarah Guru Bimbingan Konseling) Kab. Pekalongan di SMA Negeri I Wiradesa Pekalongan - Mudjiyono Mudjiyono; Sudarman Sudarman; Hani Krisnawati; Endang Dwi W; Praditya Dewi A (JURNAL PENGABDIAN KEPADA MASYARAKAT SISTHANA, 2020)
The economic growth of Pekalongan Regency, which is getting better, is not followed by awareness of citizens in complying with tax payments in a timely manner and in accordance with their income. This can be seen from the level of taxpayer compliance in reporting annual tax return (SPT) taxes at KPP Pratama Pekalongan which is still lacking. Seeing the vision and mission of Pekalongan Regency, it gives encouragement to the community to continue to increase the potential of existing resources, for example in the fields of agriculture, trade, plantations, even in the field of education. Increased utilization of potential resources will lead to increased economic growth in Pekalongan Regency. Increasing economic growth is related to the awareness and compliance of Pekalongan Regency residents with taxes. This Community Service Activity (PKM) is expected to provide an introduction and encouragement for teachers to introduce and apply the importance of implementing tax compliance, both to fellow teachers, to students, and to the surrounding environment.